wood burns down - Bukh, Vladimir; Alexeev, Sergey (project baikal, 2004)
To relax the local authorities and to receive the guests of high rank «with no tie» the so-called «Fisherman’s House» was built at the source of Angara-river, near Lake Baikal. Vladimir Ivanov, a young architect, was noticed by his skillful performa nee of exclusive orders and became the author of this house. At the time of ferroconcrete boom the proposal to build a wooden guest house turned out to be unexpectedly to the point and was graciously approved. The economic department was entrusted to select the men good for carpenter’s work, and the forestry department was entrusted to provide thick round timber. And the work started. But, as it usually happens, the workers did not take the trouble and made the first eight rims of the current timber with an inappropriate diameter. And when Pavlov insisted on demolishing the construction and replacing the logs by the logs with the necessary diameter, the building work obeyed to his will and was finished suecessfully. The architecture of the house is not the derived action of the saw and the fret-saw. It is a technology of the axe. It is natural, convincing and original. It is no use to look for the local sources in it. It grew up in the area of timber and cold winter. And this clear and efficient action kept the construction from the annoying vulgarity and provided Siberian exotics easily penetrating into one’s soul, refined as it may be. One of the eminent guests said with admiration: «Even if Pavlov had created nothing more, he would have justified his professional choice with this single house.» Why not to say it as a good toast. However, this is a suitable case to add: style is an absence of style. It is a taste. After the Fisherman’s House Irkutsk architects were attracted by wood. They followed the strictness in wood and, as much as they could, created a couple of successful remakes, until the cylinder logs and ... new Russian architects appeared. With their own aesthetics. After Pavlov had left Irkutsk, near his house appeared another one, it was not a log house, and its style was glaringly unfriendly. And soon the Fisherman’s House burnt down. Not with vexation, but naturally, with smoke and fire. The author of the building next door considers the rebuilding of the lost house unpractical.